Coral reef aorta: a rare form of obstruction of the ascending aorta in adolescent with aortopathy- case report - Jha, Neerod Kumar; Raj Kumar, Benedict; Shah, Nishant; Abdullah, Osama; Al Ketan, Oraib; Harban, Fraser; Khan, Mohammad Daud (Journal of cardiothoracic surgery, 2024)
Supra aortic obstruction in children is uncommon and is seen in certain unique conditions. While intraluminal obstruction due to heavy calcification is seen in older populations, it is not described in pediatric populations. The coral reef aorta is a rare and distinct calcifying disease causing luminal obstruction of the suprarenal aorta in adults. The definition of this diagnosis relies entirely on the unique aspects and consistency of the lesions, which are rock-hard, irregular, gritty plaques with a white luminal surface resembling a coral reef. However, no such case has been described in children. We present an adolescent boy who presented with a heavily calcified ascending aortic lesion associated with aortopathy and hypertension, 12 years after an aortic coarctation repair. The investigations included echocardiography, magnetic resonance and computer-tomographic imaging. A 3-D model was printed in order to visualize and plan surgical steps in advance for safe placement of clamps and defining the extent of resection. In addition, it provided an idea about tissue quality, thickness, spatial relationship, and orientation in relation to surrounding structures. Successful resection and replacement of the diseased segment of the aorta were achieved on cardiopulmonary bypass support. Post-operative recovery was uneventful, and at 6-month follow-up, the patient is doing well. In this report, various aspects of such lesions have been discussed, including clinical presentations, complications, planning and conduct of a safe cardiopulmonary bypass, and precautions during surgery for a successful outcome. Complicated obstructive aortic lesions in children require careful assessment, appropriate advanced imaging, and the use of 3-D printing technology in order to plan and perform safe and effective surgical management. The etiology of severe calcified aorta in children may be related to metabolic factors, previous surgery, use of a homograft, or an inflammatory process. However, it has yet to be proven.